From Goethe to Gundolf : Essays on German Literature and Culture. - Paulin, Roger (Cambridge, UK : Open Book Publishers, 2021)
From Goethe to Gundolf: Essays on German Literature and Culture is a collection of Roger Paulin's groundbreaking essays, spanning the last forty years. The work represents his major research interests of Romanticism and the reception of Shakespeare in Germany, but also explores a broader range of themes, from poetry and the public memorialization of poets to fairy stories - all meticulously researched, yet highly accessible.
Intro -- Foreword -- Goethe and Schiller: Goethezeit -- 1. Goethe: Die Leiden des jungen Werthers -- 2. Goethe and Stolberg in Italy: The Consequences for Romantic Art -- 3. Schiller: Wallenstein -- 4. Laocoon, Dante, Shakespeare, August Wilhelm Schlegel and the Overcoming of Tragedy -- 5. Adding Stones to the Edifice: Patterns of German Biography -- 6. Kleist's Metamorphoses. Some Remarks on the Use of Mythology in Penthesilea -- 7. Goethe, the Brothers Grimm and Academic Freedom -- ROMANTICISM -- 8. Fairy Stories for Very Sophisticated Children: Ludwig Tieck's Phantasus -- 9. Gundolf's Romanticism -- NINETEENTH CENTURY -- 10. Some Remarks on the New Edition of the Works of Wilhelm Müller -- 11. Heine and Shakespeare -- 12. The 'Schillerfeier' of 1859 and the 'Shakespearefest' of 1864. With Some Remarks on Theodor Fontane's Contributions -- 13. Under the Horse's Tail: The Poets, Statuary and the Literary Canon in Nineteenth-Century Germany -- POETRY -- 14. Friedrich Gottlieb Klopstock: 'Der Zürchersee' -- 15. Annette von Droste-Hülshoff -- 16. Rilke: Duino Elegy Ten: In memoriam Leslie Seiffert, 1934-90 -- BOOKS -- 17. Julius Hare's German Books in Trinity College Library, Cambridge -- Bibliography -- List of Illustrations -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books